Interindividual differences in the intraindividual association of competence and well‐being: combining experimental and intensive longitudinal designs - Neubauer, Andreas B.; Lerche, Veronika; Voß, Andreas (Journal of personality, 2018)
Abstract: Objective: The aim of the present study is to assess whether people differ in the degree to which their well-being is affected by fulfillment of the need for competence. Specifically, we want to examine (a) whether interindividual differences in the within-person coupling of competence satisfaction and well-being (competence satisfaction effect) and of competence dissatisfaction and well-being (competence dissatisfaction effect) exist, and (b) whether these differences moderate the effects of an experimentally induced frustration of the need for competence. Method: A daily diary study (N=89) and a laboratory based experiment (N=150) were conducted to investigate interindividual differences in need effects. In a third study, participants of an additional daily diary study (N=129) were subsequently subjected to an experimental frustration of the need for competence. Results: Including interindividual differences in the within-person coupling of need fulfillment and well-being improved model fit significantly, indicating that there were statistically meaningful interindividual differences in need effects. The interaction of competence satisfaction effect and competence dissatisfaction effect moderated the effect of an experimental competence frustration on negative affect. Conclusion: Results show that interindividual differences in the association of competence fulfillment and well?being are a matter of degree, but not quality. They also support the claim that need satisfaction and dissatisfaction are more than psychometric opposites.